Pendampingan Pengelolaan Usaha Akomodasi di Bidang Front Office dan Housekeeping di Desa Wisata Melinggih Kelod Payangan Gianyar Bali - Diwyarthi, Ni Desak Made Santi; Suastini , Ni Made; Pinaria , Ni Wayan Chintia; Sulistyawati, Ni Luh Ketut Sri; Jata, I Wayan; Loanata , Cahyo Purnomo; Pratiwi , Kadek Andita Dwi; Wiartha, Nyoman Gede Mas; Kalpikawati , Ida Ayu; Sadjuni , Luh Gde Sri; Pratama , I Wayan Adi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
The purpose of this community service activity is to improve the technical competence and behavior of accommodation managers so that they are able to provide services that are in accordance with hotel industry standards while being based on local values ??and sustainability principles. The training, which was held on April 4-5, 2025, involved 30 members of the local community. The method used refers to the Community Empowerment and Learning by Doing approaches, supported by the theories of Excellent Service, Behavioral Competency, Expectancy Theory, Hospitality Experience, SERVQUAL, and Sustainable Tourism Development. The results of this mentoring show an increase in participants' understanding and skills in standard operating procedures for guest services and awareness of the importance of sustainability principles. This training is expected to form more competent, independent village tourism human resources that are ready to compete in the hotel industry while still upholding local Balinese values.